Le Niveau Optimal d’Entrée au Programme d’Immersion: Compte Rendu - LeScieller, Daniel (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2006)
This paper is a summary of the presentations made by the three panellists who discussed the optimal entry level into French immersion programs for Canadian children. Joan Netten presented the different points of entry into immersion programs (early, middle and late immersion) and discussed the advantages and disadvantages of each program. In her opinion, there is no clear-cut answer to the question of which is the best program. David MacFarlane outlined the French L2 programs offered in New Brunswick public schools. Laurie Carlson Berg broached the topic from a parental perspective. She dealt with the benefits of immersion programs and raised questions about the equitable offering of immersion programs across Canada. Résumé Ce compte rendu rapporte le contenu des présentations livrées par les trois panélistes invités à discuter de la question du niveau optimal d’entrée en immersion française pour les enfants canadiens et des discussions qui ont suivi. Joan Netten présente les avantages et inconvénients d’entreprendre un apprentissage scolaire immersif au niveau précoce, intermédiaire et tardif et souligne la difficulté de faire un choix absolu. David MacFarlane brosse un tableau des programmes de français L2 dispensés dans les écoles publiques du Nouveau-Branswick. Laurie Carlson Berg aborde la question du point de vue des parents et soulève des questions touchant les bénéfices obtenus de l’immersion et l’équité relativement à ces programmes.